Analisis Pertumbuhan Anggur Laut (Caulerpa sp) dengan Metode Budidaya pada Kotak Plastik - Bara, Grace Lady First; Ratoe Oedjoe, Marcelien Dj; Turupadang, Welem (Nusa Cendana University, 2024)
Caulerpa sp., a macroalgae from the Chlorophyceae class, represents a significant marine biological resource. In order to meet increasing market demands, sea grape cultivation has expanded through various methods, aiming to ensure production is not reliant on natural conditions. This study explores alternative cultivation by using container boxes and nutrient manipulation via fertilization to enhance the growth and production of Caulerpa sp. Specifically, the research examines the impact of different Bali Organiculture Guano liquid organic fertilizer dosages on Caulerpa sp. growth, identifying the optimal dosage for maximum growth. A completely randomized design with four treatments (A: control, B: 0.22 ml/l, C: 0.28 ml/l, D: 0.34 ml/l) and three replications were employed. Growth metrics were analyzed using ANOVA and post-hoc tests (BNT). Results indicated significant effects of fertilizer application on daily growth (A=1±0.00a, B=1±0.33b, C=2±0.00c, D=2±0.00d), absolute growth (A=38±0.88a, B=72±2.31b, C=85±2.65c, D=104±2.52d), Caulerpa length (A=1.2±0.03a, B=2.4±0.32b, C=3.0±0.07c, D=3.5±0.09c), and number of ramuli (A=22.4±0.21a, B=35.0±1.26b, C=43.0±4.31b, D=65.3±4.13c). The findings confirm that Bali Organiculture Guano liquid organic fertilizer significantly enhances the growth rate, absolute weight, length, and ramuli number of Caulerpa sp. in cultivation media. Keywords: Caulerpa sp, box container, growth and organic fertilizer